Proteomics based search for novel SIK2 substrates involved in endoplasmic reticulum homeostasis - Şeker, Tuncay. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2017., 2017)
As a result of high calorie diet and low physical activity, obesity has become widespread worldwide in the last two decades. Obesity, which is a risk factor for many diseases including diabetes, hypertension, and fatty liver, threatens human health considerably. Molecular studies aiming the treatment of obesity and related metabolic diseases are mostly concerned with the regulation of the feeding behaviours and metabolic pathways. SIK2, having a central role in metabolic pathways, is considered as a pharmacological target in the development of therapeutic drugs against metabolic diseases. Recent studies have shown that Endoplasmic Reticulum (ER) stress is involved in the pathological development of metabolic diseases and SIK2 plays a key role in maintaining protein homeostasis in response to ER stress. However, the molecular details have not yet been fully understood. In this study, to elucidate the role of SIK2 in ER stress response we searched for the novel ER-resident substrates of SIK2 by LCMS/ MS-based proteomic analysis. IRS4 and CHIP, considered as candidate proteins after proteomic analysis, were found to interact with SIK2 by co-immunoprecipitation experiments. In the subsequent co-IP experiments, it was also found that IRS4 interacts with the ER stress sensor protein IRE1. A series of experiments have been carried to further investigate the possible roles of IRS4 on ER-stress response and it has been concluded that IRS4 has a regulatory role on the XBP1-splicing activity of IRE1 and the degradation of the ERAD substrate CD3 . To sum up, results of this study reveal novel protein interactions which will help better understanding the molecular function of SIK2 in maintaining proteostasis in response to ER stress.
Keywords: Obesity.; Endonucleases.